BAGAIMANA BUDAYA KERJA PADA USAHA SURABI GAPURA KANG DYAN PURWAKARTA - Widie Triana Martha; Windi Septiyani; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty (PT Naureen Digital Education, 2023)
The purpose of this visit is to find out how the work culture is in the business. The method used is descriptive with observation. The data collection method is by interview, observation and documentation. The results of this visit were that the work culture at the Surabi Gapura Kang Dyan MSME was good, but had a few drawbacks in the parking facilities provided which were not extensive. When running a business, there are bound to be problems. These problems can be observed based on several factors, both internal factors and external factors. However, the owner and his employees will try to solve the existing problems.